Recent Advances in Antimony Sulfide-Based Nanomaterials for High-Performance Sodium-Ion Batteries: A Mini Review - Wang, Guangxin; Guo, Mingyi; Zhao, Yunchao; Zhao, Yibo; Tang, Kun; Chen, Zhijun; Stock, Heinz-Rolf; Liu, Yong (Frontiers in Chemistry, 2022)
Recently, sodium-ion batteries (SIBs) have attracted extensive attention as potential alternatives to lithium-ion batteries (LIBs) due to the abundance, even distribution, low cost, and environmentally friendly nature of sodium. However, sodium ions are larger than lithium ions so that the anode materials of LIBs are not suitable for SIBs. Therefore, many negative electrode materials have been investigated. Among them, Sb2S3-based nanomaterials have gradually become a research focus due to their high theoretical specific capacity, good thermal stability, simple preparation, and low price. In this review, the research progress of Sb2S3-based nanomaterials in the SIB field in recent years is summarized, including Sb2S3, Sb2S3/carbon composites, Sb2S3/graphene composites, and Sb2S3/MxSy composites. Furthermore, the challenges and prospects for the development of Sb2S3-based nanomaterials are also put forward. We hope this review will contribute to the design and manufacture of high-performance SIBs and promote its practical application.